2005
DOI: 10.2174/1381612053764814
|View full text |Cite
|
Sign up to set email alerts
|

AMPA Receptor Potentiators as Novel Antidepressants

Abstract: Depression affects a large percentage of the general population and can produce devastating consequences to affected individuals, families and society. Although the treatment of depression has been advanced by traditional antidepressants, improvements are needed across several dimensions (e.g., overall treatment efficacy, therapeutic onset time, and side effect profile). The alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor has an allosteric modulatory site(s) for which potent positive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 135 publications
(206 reference statements)
1
23
0
Order By: Relevance
“…These compounds (so-called AMPA receptor-positive modulators or AMPA receptor potentiators, ARPs) do not activate AMPA receptors themselves, but slow the rate of receptor desensitization and/or deactivation in the presence of an agonist (eg, glutamate and AMPA). Studies have shown that the biarylpropylsulfonamide ARPs (LY392098 and LY451616) have antidepressant effects in animal models of depression (including the application of inescapable stressors, forced-swim test, and tail-suspension-induced immobility tests), in learned-helplessness models of depression, and in animals exposed to chronic mild stress procedure (Alt et al, 2005;Li et al, 2001), Moreover, Ampalex was reported to have more rapid effect (during the first week of treatment) than fluoxetine (after 2 weeks) (Knapp et al, 2002). It is note worthy that lamotrigine has been shown to have an antidepressant effect in forced-swim test animal models (Szymczyk and Zebrowska-Lupina, 2000).…”
Section: Ampa Receptors and Affective-like Behaviormentioning
confidence: 99%
“…These compounds (so-called AMPA receptor-positive modulators or AMPA receptor potentiators, ARPs) do not activate AMPA receptors themselves, but slow the rate of receptor desensitization and/or deactivation in the presence of an agonist (eg, glutamate and AMPA). Studies have shown that the biarylpropylsulfonamide ARPs (LY392098 and LY451616) have antidepressant effects in animal models of depression (including the application of inescapable stressors, forced-swim test, and tail-suspension-induced immobility tests), in learned-helplessness models of depression, and in animals exposed to chronic mild stress procedure (Alt et al, 2005;Li et al, 2001), Moreover, Ampalex was reported to have more rapid effect (during the first week of treatment) than fluoxetine (after 2 weeks) (Knapp et al, 2002). It is note worthy that lamotrigine has been shown to have an antidepressant effect in forced-swim test animal models (Szymczyk and Zebrowska-Lupina, 2000).…”
Section: Ampa Receptors and Affective-like Behaviormentioning
confidence: 99%
“…GluR1 phosphorylation is transiently increased by stress, possibly contributing to the stress-induced facilitation of memory [122] . In addition, the AMPAR potentiators LY392098 and LY451646 have antidepressant effects in the FST and TST [123][124][125] .…”
Section: Targeting Amparsmentioning
confidence: 99%
“…GluR1 phosphorylation is transiently increased by stress, possibly contributing to the stress-induced facilitation of memory [122] . In addition, the AMPAR potentiators LY392098 and LY451646 have antidepressant effects in the FST and TST [123][124][125] .Enhanced phosphorylation of GluR1 has been detected following fluoxetine, imipramine, and ketamine treatment, and ketamine rapidly increases postsynaptic AMPAR expression [103,104,115] . Moreover, the onset of ketamine effects requires AMPARs, as the antidepressant-like behaviors are attenuated by pre-treatment with the AMPAR antagonist NBQX in mouse models of depression [116] .…”
mentioning
confidence: 99%
“…The antidepressant fluoxetine positively modulate AMPA receptors 26) . Positive AMPA receptor modulators (potentiators) produced antidepressant-like effects in the FST and tail suspension test (TST) 27) . Moreover, 2,3-dihydroxy-6-nitro-7-sulfoamoylbenzo(ƒ)quinoxaline (NBQX), an AMPA receptor antagonist, has been found to block the antidepressant-like effect of the NMDA receptor an-SS Hong, SH Cho 283 tagonists 28,29) , which suggests that this effect may be mediated by an increased AMPA-to-NMDA receptor throughput in neuronal circuits 28) .…”
Section: Introductionmentioning
confidence: 99%